Anthelmintic activity of 1,10-phenanthroline-5,6-dione-based metallodrugs - Maria E. Cirino; Thainá R. Teixeira; Alessandro M. H. Silva; Ana C. C. Borges; Lucas Fukui-Silva; Luis G. Wagner; Christiane Fernandes; Malachy McCann; André L. S. Santos; Josué de Moraes (Scientific Reports)
Abstract Parasitic worm infections impose a significant public health burden, affecting over 2 billion people, particularly in low-income regions. The limited efficacy of current treatments highlights the urgent need for new anthelmintic agents. This study investigates the potential antiparasitic activity of 1,10-phenanthroline-5,6-dione (phendione) and its metal complexes, [Cu(phendione)3](ClO4)2.8H2O and [Ag(phendione)2](ClO4), against Schistosoma mansoni, the causative agent of intestinal schistosomiasis, and Angiostrongylus cantonensis, responsible for eosinophilic meningitis in humans. Additionally, the compounds were tested on Caenorhabditis elegans, a model organism for drug discovery. All compounds exhibited strong antiparasitic activity, with Cu-phendione showing the greatest potency (EC50 = 2.3 µM for S. mansoni and 6.4 µM for A. cantonensis). Ag-phendione also demonstrated significant activity, achieving EC₅₀ values of 6.5 µM against S. mansoni and 12.7 µM against A. cantonensis. The lethal dose (LD50) values in C. elegans were over 40 times higher, indicating selective antiparasitic effects. Cytotoxicity assays using Vero cells revealed a low toxicity profile and a high selectivity index. Given the promising biological properties of phendione and its metal complexes, these findings contribute to the growing body of research seeking to address the urgent need for new anthelmintic therapies.